2018
DOI: 10.1002/brb3.1082
|View full text |Cite
|
Sign up to set email alerts
|

Obstetric anesthesia/analgesia does not affect disease course in multiple sclerosis: 10‐year retrospective cohort study

Abstract: ObjectivesMultiple sclerosis (MS) often occurs in young women and the effect of obstetric anesthesia/analgesia on the disease is poorly understood. No previous study has investigated the course of the disease in women in labor in the Czech Republic. The aim of this study was to evaluate the occurrence or absence of relapses in the 6‐month postpartum period in MS parturients with and without obstetric anesthesia/analgesia.Materials and MethodsWe retrospectively studied all deliveries (n = 58,455) at the Univers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 30 publications
0
12
0
3
Order By: Relevance
“…This could also be transferred to MS patients with THA under general anesthesia. From the field of obstetrics, there is evidence that regional and spinal anaesthesia can be used as successfully as general anaesthesia in existing MS without increasing the risk of postoperative worsening of MS symptoms [23,24]. Since the local anaesthetics used in regional and spinal anaesthesia forms share physiological properties such as the antiexcitatory effect with the pentapeptides that are increased in cerebrospinal fluid in MS, the occurrence of MS symptoms, especially in spinal anaesthesia, is theoretically possible [25].…”
Section: Role Of Anaesthesiamentioning
confidence: 99%
“…This could also be transferred to MS patients with THA under general anesthesia. From the field of obstetrics, there is evidence that regional and spinal anaesthesia can be used as successfully as general anaesthesia in existing MS without increasing the risk of postoperative worsening of MS symptoms [23,24]. Since the local anaesthetics used in regional and spinal anaesthesia forms share physiological properties such as the antiexcitatory effect with the pentapeptides that are increased in cerebrospinal fluid in MS, the occurrence of MS symptoms, especially in spinal anaesthesia, is theoretically possible [25].…”
Section: Role Of Anaesthesiamentioning
confidence: 99%
“…Two studies totalling 419 deliveries in women with multiple sclerosis (MS) (239 VD – 57%), and with neuraxial anaesthesia in 74 women (18%) found no association between mode of delivery or method of analgesia/anaesthesia and the risk of postpartum relapse or disability progression. 48,74 A 2019 UK consensus statement on pregnancy in MS concluded that MS should not influence the mode of delivery or analgesia/anaesthesia unless there was significant disability. 75 In women with severe spinal cord disease, autonomic dysreflexia should be considered in the differential diagnosis of preeclampsia.…”
Section: Resultsmentioning
confidence: 99%
“…A retrospective cohort study from the Czech Republic included 70 pregnancies to 65 women with MS and compared the impact of delivery mode (vaginal vs cesarean delivery) and type of anesthesia on the course of MS six months postpartum. No difference in postpartum relapses was found when comparing vaginal deliveries with cesarean deliveries in women with MS[115].…”
mentioning
confidence: 84%